اتجاهات أساتذة التعليم الابتدائي نحو تدريس منهاج الجيل الثاني دراسة ميدانية بمدينة الأغواط - غربي سعدة; خخاز زهرة; كروم خميستي (My University, 2022)
This study aims to know the attitudes of its primary education teachers towards teaching the second generation curriculum , we have dealt with the knowledge of the differences between the professors in their attitudes toward these curricula according to gender and professional experience, in this study we adopted the descriptive appropriate to its nature. -The sample of the study was randomly selected, consisting of 60 professors and a teacher in the primary stage in the city of laghouat . 1-There are no statistically significant differences in attitudes teachers of primary education by gender differences. 2-There are no statistically significant differnces in the attitudes of teachers of primary education according to professional experience. -To answer the hypotheses of the study, the data was collected using the 21 paragraph questionnaire, the validity of the questionnaire was verified using the alpha kronbach method, we then entered and processed the data using the statistical data SPSS program, we used the differential analysis to determine the differences between more than two groups, the results of the study were as follows: 1-There are no statistically significant differences in attitudes teachers of primary education by gender differences. 2-There are no statistically significant differnces in the attitudes of teachers of primary education according to professional experience.